The Effect of Artificial Intelligence Literacy and Entrepreneurial Orientation on the Sustainability of MSMEs in Bengkulu City - Karona Cahya Susena; Nenden Restu Hidayah (Universitas Dehasen Bengkulu, 2026)
This study examines the effect of artificial intelligence (AI) literacy and entrepreneurial orientation on the business sustainability of micro, small, and medium enterprises (MSMEs) in Bengkulu City. The rapid diffusion of AI-based tools for marketing, financial recording, and customer service has not been matched by an adequate understanding of AI among local MSME actors, while entrepreneurial orientation is believed to determine how adaptively a business responds to disruption. A quantitative associative approach was used, involving 110 MSME owners selected through purposive sampling. Data were collected using a validated and reliable questionnaire and analyzed using multiple linear regression. The results show that AI literacy and entrepreneurial orientation each have a positive and significant effect on business sustainability, and together explain 56.8% of the variance in sustainability. AI literacy was found to be the more dominant predictor. These findings imply that strengthening AI-based digital skills alongside an innovative, proactive, and risk-taking entrepreneurial mindset is essential for the long-term sustainability of MSMEs in Bengkulu City.